2019
DOI: 10.1038/s41467-019-12565-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeted knock-in mice expressing the oxidase-fixed form of xanthine oxidoreductase favor tumor growth

Abstract: Xanthine oxidoreductase has been implicated in cancer. Nonetheless, the role played by its two convertible forms, xanthine dehydrogenase (XDH) and oxidase (XO) during tumorigenesis is not understood. Here we produce XDH-stable and XO-locked knock-in (ki) mice to address this question. After tumor transfer, XO ki mice show strongly increased tumor growth compared to wild type (WT) and XDH ki mice. Hematopoietic XO expression is responsible for this effect. After macrophage depletion, tumor growth is reduced. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 65 publications
0
30
0
2
Order By: Relevance
“…For chondrocyte isolation, C57BL/6 (Charles River) or XOR mutant knock-in (ki) mice, either XDH ki or XO ki, generated by introducing C995R mutation or W338A/F339L mutations in Xdh gene respectively were used ( Kusano et al, 2019 ). For experimental OA, 12-weeks old C57BL/6 female mice were subjected to medial meniscectomy (MNX) of the right knee, while the contralateral knee was sham-operated as control ( Kamekura et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For chondrocyte isolation, C57BL/6 (Charles River) or XOR mutant knock-in (ki) mice, either XDH ki or XO ki, generated by introducing C995R mutation or W338A/F339L mutations in Xdh gene respectively were used ( Kusano et al, 2019 ). For experimental OA, 12-weeks old C57BL/6 female mice were subjected to medial meniscectomy (MNX) of the right knee, while the contralateral knee was sham-operated as control ( Kamekura et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Formation of ROS within chondrocytes can play a role in ageing and OA via induction of metalloproteases (MMPs), inflammation and apoptosis ( Lepetsos and Papavassiliou, 2016 ). We have previously shown that xanthine oxidoreductase (XOR) is a cellular source of ROS that impacts on inflammasome activation ( Ives et al, 2015 ) as well as immune regulation ( Kusano et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…XOR can be found in two inter-convertible forms: (1) xanthine oxidase (XO) is an O 2 •− -mediated type that uses oxygen and generates O 2 •− , while (2) xanthine dehydrogenase (XDH) is an NAD + -mediated type that uses NAD + as a cofactor and leads to reduced nicotinamide adenine dinucleotide production but not the generation of O 2 •− [ 20 ]. These two types of XOR differ in the structure of the active site loop and the loop containing flavin adenine dinucleotide and molybdenum domains [ 21 ]. Pharmacological intervention with XO inhibitors has shown that XO is involved in various acute-injury models, such as ischemia-reperfusion injury [ 22 , 23 ], hyperglycemic cardiomyopathy [ 24 ], and neurodegeneration induced by spinal cord injury [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since XOR-knockout mice die within six weeks after birth due to renal failure [ 26 ], it is difficult to elucidate the role of XOR in vivo. To clarify the pathophysiological contribution of XOR, Kusano et al generated two types of knock-in (KI) mice for XO-locked- or XDH-stable KI mutations [ 21 ]. The XO-locked-type mice that generate O 2 •− , but not the XDH-stable-type mice that do not generate O 2 •− , showed markedly increased tumor growth associated with the activation of macrophages [ 21 ].…”
Section: Introductionmentioning
confidence: 99%